Î±g_á»Š-open sets and Î±g_á»Š-functions - G. Saeed, Sufyan; B. Esmaeel, R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The objective of this paper is to show modern class of open sets which is an -open. Some functions via this concept were studied and the relationships such as continuous function strongly -continuous function -irresolute function -continuous function.